STUDIES ON DRY MATTER, ENERGY AND PROTEIN UTILIZATION OF THREE BREEDS OF DAIRY COWS AT IBADAN (1976)
Comparative studies were conducted on exotic (German Brown and Friesian) and indigenous (White Fulani) lactating cows to assess (a) the systems of management best suited for the newly imported lactating, exotic cows for maximum production (b) the effects of seasons, stage of lactation, breeds and diets on feed dry matter (DM) intake, liveweight changes, milk yield and composition, respiration and body temperature of White Fulani (WF), German Brown (GB) and Friesian (F) lactating cows and (c) the effects of DM intake, dietary level, stags of lactation and breed on productivity, digestibility of feed, milk composition, energy and protein utilization, rumen and blood metabolites. Results on management studies indicated that the grazed cows produced more milk, solids-corrected milk (SCM), butter- fat, ash and less milk protein than the stall-fed (P<.05). Although higher respiratory counts, water intake and body temperatures were recorded for the grazed cows than the stall-fed ones, the results were not statistically significant (P> 0.05) Lactation studies showed that the exotic breeds consumed more forage DM than the indigenous, giving 5.92±0.21, 5.59±0.l6 and 4.49±0.16kg/day for the F, GB and WF cows respectively. The peak forage DM intake was attained between the 5th and 10th week of lactation. The mean milk yield and SCM were 27.55±6.15 and 29.83±5.26kg/week respectively for the WF cows, 40.16±6.15 and 36.91±3.26 respectively for the F and 41.16±8.19 and 40.16±5.84kg/week respectively for the GB. Peak milk production was attained between the 5th and 9th week of lactation. Generally, results showed that the milk of the WF cows possessed higher milk quality, producing higher percentage of butterfat and protein, than the exotic breeds. Although there were more forage DM intake during the dry season than the wet, higher milk yield was recorded during the latter season than the former. Liveweight losses occurred from the beginning of the experiment to about the 10th week of lactation. The results of the relationship between rumen metabolites and milk yield showed that when the ratio of acetate to propionate was lower, there was a higher yield of milk and protein but when the ratio was higher, there was an increased butterfat. The digestible crude protein'(DCP) values for maintenance were 0.39g/day/W(0.734 kg) (91.82g/day available protein (AP), O.47g/day/(0.734 kg) (113.28g/day AP) and 0.52g/day/(0.734 kg) (121.77g/day AP) for the WF, GB and F cows respectively. The N-balance studies indicated that 6.69gDCP/day/W(0.734 kg) (304.80gAP/day) were required by the WF cows to produce 3.35kg milk/day (0.51%N), 6.34DCP/day/W(0.734 kg) (353.93gAP/day) by the GB cows to produce 6.17kg milk/day (0.47%N) and 6.54gDCP/day/W(0.734 kg) (359.20g AP/day) by the F cows to produce 7.08kg milk/day (O.49%N). The mean net efficiency of protein utilization were 27.95, 43.43 and 53.73% for the WF, GB and F cows respectively. The metabolizable energy values for maintenance were 0.53, 0.59 and 0.61 MJ/day/W(0.734 kg) for the WF, GB and F cows respectively. These are 72.29, 72.75 and 73.43% of the Ministry of Agriculture, Fisheries and Food of the United Kingdom (MAFF)(1975) recommendation respectively. The gross energetic efficiencies for milk production were 10.23, 12.79 and 14.33% for the WF, GB and F cows respectively while the net energetic efficiencies were 25.47, 31.31 and 37.50% respectively. Finally, the conclusions from the trials have shown that 8.3% (WF), 10.3% (F) and 11.2% (GB) of the energy intake were contributed by the protein fraction of the DM intake.